Cross-kingdom microRNA transfer for the control of the anthracnose disease in cassava - Pinweha N. (2023)
Cassava anthracnose disease (CAD), caused by Colletotrichum gloeosporioides f. sp. manihotis, is one of the most important diseases that cause significant yield loss in cassava. Recently, involvement of microRNAs (miRNAs), a class of small, single-stranded, non-coding RNAs, in the resistance against anthracnose disease has been indicated. In this study, two cassava cultivars that have different degree of CAD susceptibility were utilized to investigate the differences in defense responses these cultivars exhibited and to examine the role of seven miRNA families (mes-MIR156, 159, 164, 171, 396, 408, and 530) during CAD infection. Unlike the susceptible cultivar, the tolerant cultivar responded to fungal attack in the forms of hypersensitive response at the primary site of infection (or stem), as well as systemic induction of different defensive measures in the distal organs (or leaves) such as callose deposition, H2O2 accumulation, and upregulated expression of the miRNAs being studied. Two of the miRNAs, mes-MIR156 and mes-MIR164, were able to move across the kingdom boundary to the invading fungal cells. With the availability of genome sequence of C. gloeosporioides strain Cg-14, the mes-MIR156 and mes-MIR164 were predicted to target five and eleven fungal genes, respectively. Based on the differences in defense responses observed in the CAD-tolerant and CAD-susceptible cultivars, we then propose that the tolerant cultivar possesses a distinct defense mechanism against C. gloeosporioides f. sp. manihotis infection. In this defense mechanism, certain miRNAs are needed to help protect the host plant from the invading fungal pathogen.